Esterases From Bifidobacteria Exhibit the Conversion of Albiflorin in Gut Microbiota - Peng, Ran; Han, Pei; Fu, Jie; Zhang, Zheng-Wei; Ma, Shu-Rong; Pan, Li-Bin; Xia, Yuan-Yuan; Yu, Hang; Xu, Hui; Liu, Chang-Xiao; Wang, Yan (Frontiers in Microbiology, 2022)
Bifidobacteria is an important microbe that inhabits the human gut. It is capable of metabolizing complex compounds in the human diet. Albiflorin, an antidepressant natural product from Radix Paeoniae Alba in China, is difficult to absorb after oral administration, and its metabolism has been proven to be closely related to the gut microbiota. In this study, we demonstrated in vitro that several Bifidobacteria species were able to convert albiflorin to benzoic acid, and four esterases (B2, B3, B4, BL) from Bifidobacterium breve and Bifidobacterium longum were found through genome mining and modeled by SWISS-MODEL. B2 and B3 presented the strongest albiflorin metabolism ability. The optimal conditions, including temperature, buffer and pH, for the conversion of albiflorin by the four esterases were investigated. Furthermore, the effect of esterase on the metabolism of albiflorin in vivo was confirmed by transplanting bacteria containing esterase B2. This study demonstrated the vital role of esterases from Bifidobacteria in the metabolism of natural compounds containing ester bonds, which could contribute to the development of new enzymes, microbial evolution and probiotic adjuvant compounds for treatment.